Targeting and retention of HPV16 E7 to the endoplasmic reticulum enhances immune tumour protection - Loera Arias, María de Jesús; Martínez Pérez, Alejandra Guadalupe; Barrera Hernández, A.; Ibarra Obregón, E. R.; González Saldívar, Gerardo; Martínez Ortega, Jesús Iván; Rosas Taraco, Adrián Geovanni; Villanueva Olivo, Arnulfo; Esparza González, Sandra Cecilia; Villatoro Hernández, Julio; Saucedo Cárdenas, Odila; Montes de Oca Luna, Roberto (2009)
The endoplasmic reticulum (ER) is where the major histocompatibility complex (MHC) class I molecules are loaded with epitopes to cause an immune cellular response. Most of the protein antigens are degraded in the cytoplasm to amino acids and few epitopes reach the ER. Antigen targeting of this organelle by Calreticulin (CRT) fusion avoids this degradation and enhances the immune response. We constructed a recombinant adenovirus to express the E7 antigen with an ER-targeting signal peptide (SP) plus an ER retention signal (KDEL sequence). In cell-culture experiments we demonstrated that this new E7 antigen, SP-E7-KDEL, targeted the ER. Infection of mice with this recombinant adenovirus that expresses SP-E7-KDEL showed interferon induction and tumour-protection response, similar to that provided by an adenovirus expressing the E7 antigen fused to CRT. This work demonstrated that just by adding a SP and the KDEL sequence, antigens can be targeted and retained in the ER with a consequent enhancement of immune response and tumour protection. These results will have significant clinical applications.